2021
DOI: 10.1371/journal.pone.0249853
|View full text |Cite|
|
Sign up to set email alerts
|

Knowledge, attitude, perception, and preventative practices towards COVID-19 in sub-Saharan Africa: A scoping review

Abstract: Background Knowledge, attitudes, perception, and preventative practices regarding coronavirus- 2019 (COVID-19) are crucial in its prevention and control. Several studies have noted that the majority of people in sub-Saharan African are noncompliant with proposed health and safety measures recommended by the World Health Organization (WHO) and respective country health departments. In most sub-Saharan African countries, noncompliance is attributable to ignorance and misinformation, thereby raising questions abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
45
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 43 publications
9
45
1
2
Order By: Relevance
“…Especially in the South Asian and Oceania region, participants who did attend university are scored lower. These findings were consistent with other studies where the authors found poor knowledge about the infectious disease among non-graduate populations (Nwagbara et al, 2021 ; Wang et al, 2018 ). We found significant differences in overall and Middle East regional knowledge scores by educational status.…”
Section: Discussionsupporting
confidence: 93%
“…Especially in the South Asian and Oceania region, participants who did attend university are scored lower. These findings were consistent with other studies where the authors found poor knowledge about the infectious disease among non-graduate populations (Nwagbara et al, 2021 ; Wang et al, 2018 ). We found significant differences in overall and Middle East regional knowledge scores by educational status.…”
Section: Discussionsupporting
confidence: 93%
“…The public's positive perceptions were correlated with self-reported adherence to home-quarantine, acknowledging thus the relation between beliefs and behavior, in agreement with established findings 29 . Similarly to previous research, females appeared more likely to consider NPI important, scored better in awareness questions 8 , held more positive attitudes 30 and adherence levels to COVID-19 mitigation strategies 7 . Also, respondents from Athens demonstrated higher perceived importance of NPI, like the residents of Hubei when compared with people from other areas of China 7 .…”
Section: Discussionsupporting
confidence: 69%
“…In the ongoing COVID-19 pandemic, even though vaccines have been rolled out and the vaccination campaigns in some countries have already been followed by a decline in number and severity of cases 4 , non-pharmaceutical interventions (NPI) are still playing an important role on COVID-19 management, such as social distancing through lockdown of institutional and professional facilities, and entertainment venues, or personal hygiene measures such as frequent hand washing 5,6 . Existing literature provides strong evidence that individuals' perception of NPI plays a major role in successful disease mitigation 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…The people in sub-Saharan Africa have adequate knowledge about COVID-19, but there is a significant gap in their perception toward COVID-19 and utilization of prevention measures. 39 In Ethiopia, people infected with SARS-CoV-2 have been increasing significantly despite government mitigation measures. 40 As of May 14, 2021, over 264,000 confirmed cases and 4000 deaths have been reported.…”
Section: Discussionmentioning
confidence: 99%